Spatio-temporal Analysis of Drought Trends Recorded during the Wettest Months in the Mouhoun-Comoé Basin in Burkina Faso (Africa): an Analysis using Z-score and Linear Regression - Yameogo, Joseph (Geographica Pannonica, 2025)
Meteorological drought is a natural phenomenon that occurs when there is insufficient rainfall over a more or less prolonged period. In West African countries, and particularly in Burkina Faso, this situation undermines agricultural systems. Knowledge of the spatio-temporal trends of drought is essential for optimal management of water resources and effective planning of sustainable agricultural activities. The aim of this study is the analysis of the spatio-temporal trends of drought in the Mouhoun-Comoé basin in Burkina Faso. To this end, the study used CHIRPS rainfall data in raster and CSV file form for July and August, as well as soil moisture (0-10 cm) at 1-, 2- and 3-month scales for the period 1994-2024. The data were analysed using the z-score index, linear regression and correlation. The study shows that the upward trend in drought oscillates between extreme drought and mild drought. The decade 1994-2004 was characterised by extreme drought, followed by a decrease in drought throughout the basin during the decade 2005-2014. Finally, in the decade 2015-2024, a phase of high humidity was observed throughout the basin. Drought trends have had an impact on soil moisture levels, particularly in the valleys of the basin. This situation has a negative impact on agricultural production in the basin. This situation is forcing farmers to use crops that have more or less water tolerance in order to cope with the drought.
Keywords: drought; soil moisture; z-score; linear regression; correlation; Mouhoun-Comoé basin; Africa